Vaccine-induced immune thrombotic thrombocytopenia: definition, risks with different vaccines, and regulatory responses - S. V. Akinshina; V. O. Bitsadze; J. Kh. Khizroeva; K. N. Grigorieva; E. V. Slukhanchuk; M. V. Tretyakova; V. I. Tsibizova; I. Elalamy; J.-C. Gris; B. Brenner; E. Grandone; C. Ay; et al. (Акушерство, гинекология и репродукция)
After the vaccination campaign initiation in Europe and the UK, reports of rare cases of atypical thrombosis, including sinus vein thrombosis and splanchnic venous thrombosis, began to appear in association with the use of vector vaccines AstraZeneca (ChAdOx1) and Johnson & Johnson/Janssen. The syndrome called VITT (vaccine-induced immune thrombotic thrombocytopenia) manifested as thrombosis simultaneously with a decrease in platelet count, a significant increase in D-dimer levels and a detection of factor 4 platelet (PF4) antibodies. We present a detailed review of the epidemiology, pathogenesis, clinical presentation, diagnostics and treatment of VITT, which is by its nature an immune complication, similar to the processes occurring in heparin-induced thrombocytopenia (HIT). All international and national organizations and regulatory authorities, including experts in the field of thrombosis and hemostasis and the VITT expert council recommend continuing the prompt mass vaccination against COVID-19 as the only method that can reduce the incidence of severe cases, stop the spread of COVID-19 infection and the emergence of new dangerous mutations in the viral genome. Failure to vaccinate poses an incomparably greater risk of fatal thrombotic and inflammatory complications associated with infections, compared with the risks of extremely rare adverse events that can occur after vaccination. It should be noted that information on VITT, described as a sporadic phenomenon of an abnormal immune response to some variants of vaccines against COVID-19, cannot be translated to other vaccines (including registered in the Russian Federation) and even more cannot be a reason for refusal to use them.